„KRYZYS MONARCHI PIASTOWSKIEJ” I PROBLEM TZW. REAKCJI POGAŃSKIEJ OKIEM ARCHEOLOGA - Kajkowski, Kamil (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The turmoil of the 1030s in the Polish territory has so far attracted attention of historians. A detailed analysis of the information available in the written sources has strengthened a position in the result of which (in line with the reference to the events in question) the pagan backlash was to stem primarily from religious reasons. This interpretations suggests and provokes reception of Mieszko II’s domain as a completely Christian organisation. Consequently, at least officially it suggests that the pagan communities had been pushed to the margins of the society. Scholars have no doubts that these communities existed because they are regarded to have affected the events of the 1030s. Was it really the case? An analysis of archaeological sources, previously not used in the discussion of the pagan backlash, does not answer the questions so unambiguously. There is a strong indication that the followers of the old values did not have to flee from persecutions or the missionary ideology. It also looks like they did not have to fear financial exploitation for the benefit of the established church structures which could have easily operated parallel to venues referring to the traditional religious symbols. If we assume that it was the case, were the events of the 1030s in fact a pagan backlash? This question was at the basis of the considerations presented in this text.